Alfabetização científica sobre a degradação dos recursos hídricos por meio do ensino por investigação no ensino médio - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The rates of environmental degradation in the last century have become an alarming issue for the whole world. As a result, phenomena such as natural disasters, climatic catastrophes and the acute shortage of resources that are essential for maintaining life on Earth are becoming increasingly notorious. The sense of nonconformity was not established by or against man in relation to his unsustainable exploitation of natural resources. Much of this is due to the mistaken belief that natural resources are infinite and inexhaustible. Among these resources, water stands out as a finite and indispensable resource for life as we know it. In this sense, studying this subject in elementary school can contribute to the formation of scientifically literate citizens and promote greater care and sustainable use of water. The aim of this study was to evaluate and analyze the use of an investigative approach as a teaching strategy to promote scientific literacy on the subject of water resource degradation in 2022 in a public high school class at a full-time teaching center in Anápolis-GO. The research participants were 23 students from a different 1st year high school class, aged between 15 and 17, who were able to participate and met the standards set by UEG's Research Ethics Committee. The study consisted of the development and application of two investigative teaching sequences for the study of the theme described above, which were divided into four investigative moments covering different subjects of the same major theme investigated, over the course of 22 lessons of 50 minutes each. The data was evaluated using content analysis based on the interactions during the students' lessons and the activities carried out. The results showed the effectiveness of investigative activities in developing skills such as student engagement and autonomy. The active constructivist teaching modality used in this study, an Investigation Teaching Sequence, favoured the emergence of indicators of Scientific Literacy in the students, such as: logical and proportional reasoning; classification, sorting and organization of information; raising and testing hypotheses; justification; prediction and explanation.
Scientific literacy on water resource degradation through inquiry teaching in high school
Keywords: Água; Abordagem Investigativa; Cientificamente alfabetizados; Letramento científico; Water; Investigative approach; Scientifically Literate; Degradação ambiental - Recursos hidrícos; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS BIOLOGICAS